1996
DOI: 10.1177/001440299606200404
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Professionals-at-Risk: Evaluating Interventions to Reduce Burnout and Improve Retention of Special Educators

Abstract: This article describes a controlled study of92 special educators and related service providers that evaluated the effects of two interventions (a series ofstress-management workshops and a peer-collaboration program) on factors known to be correlated with actual turnover (burnout, job satisfaction, and organizational commitment). Results indicated that improvements on dependent variables occurred as a function of intervention, thus suggesting that the programs show promise as means ofproviding on-the-job suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
100
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(110 citation statements)
references
References 26 publications
5
100
0
2
Order By: Relevance
“…The other strategies include maintaining cordial relationship with colleagues, enjoying uninterrupted sound sleep up to seven or eight hours in a day as well as attending to problems as and when due. This submission is also in line with Cooley & Yovanoff (1996) who suggested, among other things, muscle relaxation, progressive body relaxation that puts the individual in an extremely restful state as a strategy for coping with stress.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The other strategies include maintaining cordial relationship with colleagues, enjoying uninterrupted sound sleep up to seven or eight hours in a day as well as attending to problems as and when due. This submission is also in line with Cooley & Yovanoff (1996) who suggested, among other things, muscle relaxation, progressive body relaxation that puts the individual in an extremely restful state as a strategy for coping with stress.…”
Section: Discussionsupporting
confidence: 82%
“…Besides, Kagan, Kagan & Watson (1995) and Cooley & Yovanoff (1996) suggested physiological coping strategies against stress. The authors suggested the following: (1) biofeedback: electronic measurement of mind-body functions (muscle tension, intestinal activity, blood flow, breathing, heartbeat) and techniques to control those functions.…”
Section: Introductionmentioning
confidence: 99%
“…As organizational contributors to the origin of burnout are very often intangible factors, intervention programs should focus on personal factors such as the individual's maladaptive way of thinking in taxing and stressful situations. This idea is in accordance with Cooley and Yovanoff (1996) who claim that intervention programs had better start from alterable factors within the burned-out teacher. It would be even a better idea to include courses on thinking processes in training programs for teachers, for self-knowledge on the various components of thinking may have a preventive and beneficial effect on the teacher's well-being during his or her career.…”
Section: Discussionsupporting
confidence: 82%
“…As discussed, employee-led work design processes appear to be especially applicable to job resources such as job autonomy, which have been characterized as 'alterables' that are easier to change (Hakanen et al, 2006;Tims, et al, 2013), but less applicable to the demanding aspects of work design that derive from higherlevel pressures (Rhoades & Eisenberger, 2002), which have been labeled as 'givens' (Cooley & Yovanoff, 1996). Thus, encouraging bottom up forms of work redesign to enhance the quality of work, such as by training individuals in job crafting (Grant & Parker, 2009) and encouraging the negotiation of i-deals (Liao et al, 2016) might have positive effects; but these effects might nevertheless be limited to some work characteristics and indeed some contexts.…”
Section: Key Themes and Theoretical Implicationsmentioning
confidence: 99%